2010
DOI: 10.1080/13504850802676207
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and the size of government: causality tests for OECD and Latin American countries

Abstract: The purpose of this article is to examine the causality between government size and corruption, and to verify if there is a different pattern of causality between developed Organization for Economic Co-operation and Development (OECD) countries (excluding Mexico) and developing countries (Latin American countries) during the period 1996 to 2003. Applying Granger and Huang's (1997) methodology we find evidence that size of government Granger causes corruption in both samples. Since a larger government involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 9 publications
0
15
0
4
Order By: Relevance
“…Similarly, another empirical study that used data sets from 100 countries over the time periods 1995 – 1997, 1998 – 2000, and 2001 – 2003 found that larger governments in fact led to lower levels of corruption (Goel and Nelson, ). Another study that uses data for both OECD and developing countries over the period 1996 – 2003 however found there to be a strong causality between large governments and corruption (Arvate et al ., ). In an attempt to explain these ambiguous results, a later study used annual data from 82 countries between 1995 and 1998 while controlling for the levels of democracy.…”
Section: Causes Of Corruptionmentioning
confidence: 97%
“…Similarly, another empirical study that used data sets from 100 countries over the time periods 1995 – 1997, 1998 – 2000, and 2001 – 2003 found that larger governments in fact led to lower levels of corruption (Goel and Nelson, ). Another study that uses data for both OECD and developing countries over the period 1996 – 2003 however found there to be a strong causality between large governments and corruption (Arvate et al ., ). In an attempt to explain these ambiguous results, a later study used annual data from 82 countries between 1995 and 1998 while controlling for the levels of democracy.…”
Section: Causes Of Corruptionmentioning
confidence: 97%
“…At the opposite pole, there are individualistic religions such as Protestantism which promote economic freedom with a less involvement of government in the private sector. Therefore, these categories of religions are less tolerant with corruption acts than in those where hierarchical religions are dominant(Arvate et al, 2009; Kilkon and Seong-Gin, 2014). A second category of studies investigates the relationship between religion and corruption starting from the level of religiosity.…”
mentioning
confidence: 99%
“…A large body of literature favours the view that increasing government size provides more opportunities for political rent‐seeking activities, therefore, leading bureaucrats to corruption (Kotera et al ). For example, Arvate et al () show that government size Granger cause corruption in a sample of OECD and Latin American countries. Bernauer and Koubi () also demonstrate that higher government spending as a percentage of GDP goes hand‐in‐hand with an inferior quality of public good offering, in their case, air quality.…”
Section: Resultsmentioning
confidence: 99%